Ex Vivo Expansion of CD34+CD90+CD49f+ Hematopoietic Stem and Progenitor Cells from Non‐Enriched Umbilical Cord Blood with Azole Compounds. (2nd February 2018) - Bari, Sudipto; Zhong, Qixing; Fan, Xiubo; Poon, Zhiyong; Lim, Alvin Soon Tiong; Lim, Tse Hui; Dighe, Niraja; Li, Shang; Chiu, Gigi Ngar Chee; Chai, Christina Li Lin; Hwang, William Ying Khee
Abstract: Umbilical cord blood (UCB) transplants in adults have slower hematopoietic recovery compared to bone marrow (BM) or peripheral blood (PB) stem cells mainly due to low number of total nucleated cells and hematopoietic stem and progenitor cells (HSPC). As such in this study, we aimed to perform ex vivo expansion of UCB HSPC from non‐enriched mononucleated cells (MNC) using novel azole‐based small molecules. Freshly‐thawed UCB–MNC were cultured in expansion medium supplemented with small molecules and basal cytokine cocktail. The effects of the expansion protocol were measured based on in vitro and in vivo assays. The proprietary library of >50 small molecules were developed using structure‐activity‐relationship studies of SB203580, a known p38‐MAPK inhibitor. A particular analog, C7, resulted in 1, 554.1 ± 27.8‐fold increase of absolute viable CD45 + CD34 + CD38 – CD45RA – progenitors which was at least 3.7‐fold higher than control cultures ( p  < .001). In depth phenotypic analysis revealed >600‐fold expansion of CD34 + /CD90 + /CD49f + rare HSPCs coupled with significant ( p  < .01) increase of functional colonies from C7 treated cells. Transplantation of C7 expanded UCB grafts to immunodeficient mice resulted in significantly ( p  < .001) higher engraftment of human CD45 + and CD45 + CD34 + cells in the PB and BM by day 21 compared to non‐expanded and cytokine expanded grafts. The C7 expanded grafts maintained long‐term human multilineage chimerism in the BM of primary recipients with sustained human CD45 cell engraftment in secondary recipients. In conclusion, a small molecule, C7, could allow for clinical development of expanded UCB grafts without pre‐culture stem cell enrichment that maintains in vitro and in vivo functionality. Stem Cells Translational Medicine 2018;7:376–393 Abstract : This study identified a novel structural analog of SB203580 (p38‐MAPK inhibitor) that expands hematopoietic stem and progenitor cells (HSPC) from non‐enriched, frozen‐thawed umbilical cord blood (UCB)–mononucleated cells. The UCB graft expanded with the lead small molecule C7 consists of primitive HSPC phenotype (CD34 + CD90 + CD49f + ), maintains enhanced in vitro colony formation capacity and engrafts both primary and secondary immunodeficient mice. If CD34 selection is further used, this molecule is also able to attain superior HSPC expansion compared to current technologies.